A Novel Plant Vacuolar Na(+)/H(+) Antiporter Gene Evolved by DNA Shuffling Confers Improved Salt Tolerance in Yeast - Xu, Kai (American Society for Biochemistry and Molecular Biology, 2010)
Plant vacuolar Na(+)/H(+) antiporters play important roles in maintaining cellular ion homeostasis and mediating the transport of Na(+) out of the cytosol and into the vacuole. Vacuolar antiporters have been shown to play significant roles in salt tolerance; however the relatively low V(max) of the Na(+)/H(+) exchange of the Na(+)/H(+) antiporters identified could limit its application in the molecular breeding of salt tolerant crops. In this study, we applied DNA shuffling methodology to generate and recombine the mutations of Arabidopsis thaliana vacuolar Na(+)/H(+) antiporter gene AtNHX1. Screening using a large scale yeast complementation system identified AtNHXS1, a novel Na(+)/H(+) antiporter. Expression of AtNHXS1 in yeast showed that the antiporter localized to the vacuolar membrane and that its expression improved the tolerance of yeast to NaCl, KCl, LiCl, and hygromycin B. Measurements of the ion transport activity across the intact yeast vacuole demonstrated that the AtNHXS1 protein showed higher Na(+)/H(+) exchange activity and a slightly improved K(+)/H(+) exchange activity.